THE ASSOCIATION BETWEEN PROJECT-BASED LEARNING AND CRITICAL THINKING SKILLS IN ELEMENTARY ISLAMIC EDUCATION - Delia Nur Aulia; Diansyah Permana; Cecep Hilman; Muhammad Khairi bin Mahyuddin (AL - IBRAH, 2026)
Traditional lecture methods in elementary Islamic Education (PAI) may not sufficiently develop the high-level analytical competencies needed for 21st-century learning environments. This study was conducted to evaluate the potential impact of implementing the Project-Based Learning (PjBL) model to systematically stimulate primary students' reasoning abilities. Employing a quantitative approach with a pre-experimental one-group pretest-posttest design, this study examined the implementation of the Project-Based Learning (PjBL) model and changes in students' critical thinking skills among 67 fifth-grade students at SD Negeri Campaka 3. Findings should be interpreted cautiously due to the absence of a control group, which limits the ability to establish causal conclusions. Data collection procedures involved distributing structured questionnaires and administering twenty validated multiple-choice academic tests, which were processed using computational statistics in SPSS. The descriptive findings reveal that the project execution achieved an 85% success rate, which significantly increased the students' analytical performance from a low baseline pretest mean of 33.81 up to an accomplished posttest average of 79.25. Inferential statistical analysis using a paired-samples t-test indicated a statistically significant difference between pretest and posttest scores (p = 0.000). The effect size analysis showed a large practical effect (Cohen's d = 4.12), although the findings should be interpreted with consideration of the pre-experimental design limitations. This study concludes that the collaborative project framework serves as a highly reliable pedagogical tool to enhance students' critical thinking skills by translating abstract curriculum themes into interactive, real-world solutions.